(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Glaucoma remains one of the leading causes of irreversible blindness worldwide, presenting a significant public health challenge. Current glaucoma management primarily relies on eye drops, with prostaglandin analogs, such as latanoprost being a cornerstone of treatment. However, patient adherence, ocular side effects, and the need for consistent dosing pose substantial obstacles to effective care. This review paper introduces a groundbreaking approach to glaucoma management through innovative latanoprost drug delivery. By leveraging cutting-edge drug delivery technologies, including sustained-release systems and advanced ocular implants, this revolutionary approach aims to address the limitations of conventional eye drops and transform glaucoma care. In conclusion, the integration of innovative latanoprost drug delivery systems holds great promise for revolutionizing glaucoma care. These advancements offer the potential to significantly reduce the burden of vision loss associated with glaucoma and improve the quality of life for affected individuals. Further research and clinical trials are essential to validate the safety and efficacy of these new approaches and usher in a new era of glaucoma management.